مشكلات الطلبة في تعلم النحو بعملية التعلم عن بعد بقسم تعليم اللغة العربية بجامعة الرانيري الإسلامية الحكومية - Aprilia, Nanda; Hamdiah, Hamdiah; Ridha, Muhammad (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2021)
This paper describe about the process of studying nahwu and the problem faced by college student of Arabic language education with distance learning system. The purpose of this study is knowing the process of studying nahwu and the problems are face by college student with distance learning system at Arabic language education. The study method has been used by researcher is descriptive qualitative method. Data were collected by deep interview and documentation. The data analysis process was held by four phases are data collection, data reduction, data presentation and deduction. The results of this study are studying nahwu with distance learning system has been used google classroom and google meet as a learning media, then the learning methods used for is a discourse method, discussion method and assignment method. The problem faced by college students are difficulties to understand the material and also difficulties to attended assignment and afraid to giving question and couldn’t focus to the subject and the last one is internet networking problem.